Poisoned tarts : a Savannah Reid mystery - McKevett, G. A. (McKevett, G. A. Savannah Reid mystery., 2008)
As Halloween approaches, P.I. Savannah Reid finds herself knee-deep in tricks and treats when a member of The Skeleton Key Three, a celebutante clique, goes missing, and the wealthy host of the annual Halloween bash is murdered.